2022
DOI: 10.1155/2022/6864195
|View full text |Cite
|
Sign up to set email alerts
|

Moxibustion for Primary Dysmenorrhea: An Adjuvant Therapy for Pain Relief

Abstract: The latest spectrum of moxibustion disease shows that primary dysmenorrhea is a high-frequency symptom of moxibustion and that it is the dominant clinical disease. In the specific treatment methods, all types of moxibustion methods have been widely used, such as thermal, thunder fire, partitioned, and spreading moxibustion. Moxibustion plays a therapeutic role through its four mechanisms of action: heat, light, moxa smoke, and drug effects. The mechanism of moxibustion treatment for primary dysmenorrhea focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
0
10
1
Order By: Relevance
“… 1 It marks the interface between girlhood and womanhood; hence, it is an important aspect of female reproductive health. 2 , 3 Unfortunately, the onset of menstruation is usually coupled with challenges that affect between 50% and 95% of women. 2 , 4 These challenges include delayed menses, irregular menstrual periods, painful menstrual periods, and heavy menstrual bleeding, among others.…”
Section: Introductionmentioning
confidence: 99%
“… 1 It marks the interface between girlhood and womanhood; hence, it is an important aspect of female reproductive health. 2 , 3 Unfortunately, the onset of menstruation is usually coupled with challenges that affect between 50% and 95% of women. 2 , 4 These challenges include delayed menses, irregular menstrual periods, painful menstrual periods, and heavy menstrual bleeding, among others.…”
Section: Introductionmentioning
confidence: 99%
“…Folium Artemisiae Argyi, commonly used in Mo, is considered a pure yang TCM. By burning, it can stimulate meridians and acupoints, facilitate transdermal drug delivery and absorption, and provide Mo and warming effects [ 111 ]. TCM attributes the occurrence and progression of dysmenorrhea to factors such as cold coagulation and blood stasis.…”
Section: Discussionmentioning
confidence: 99%
“…The current clinical and experimental research indicate that moxibustion improves the body's immunity and effectively inhibits inflammatory responses [ 42 ]. In addition, a study [ 10 ] on the mechanism of moxibustion found that moxibustion plays a therapeutic role through its four mechanisms of action: heat, light, moxa smoke, and drug effects. The mechanism of moxibustion treatment for primary dysmenorrhea focuses on adjusting endocrine hormones, regulating immune function and neuro-related factors, and improving uterine microcirculation.…”
Section: Discussionmentioning
confidence: 99%
“…e current clinical and experimental research indicate that moxibustion improves the body's immunity and effectively inhibits inflammatory responses [42]. In addition, a study [10] on the mechanism of moxibustion found that moxibustion plays a therapeutic role through its four mechanisms of action: heat, light, moxa smoke, and drug effects.…”
Section: Discussionmentioning
confidence: 99%